Pendidikan Karakter Guru PAI Kepada Moralitas Religius Siswa Sekolah Menengah Pertama - Wijaya, Deno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the character education of PAI teachers to the religious morality of junior high school students. This research uses a qualitative case study. In this study, data collection was carried out by observation, interviews, documentation, and questionnaires. A direct observation approach was used in this study, where researchers went directly to the research location to make observations and record data systematically using instruments as a guide. The research was conducted at SMP Negeri 1 Panjatan, Kulon Progo Karangasem Surakarta which is located in Gotakan, Panjatan Kec, Kulon Progo Regency, Yogyakarta. Students of SMP Negeri 1 Panjatan, Kulon Progo participated in this research. The results of this study The teacher has succeeded in instilling religious character education in students through the habituation method and applying it well to students. In improving and instilling religious character values in students, teachers take a habituation approach to students. It is known that sanctions in the form of punishment are effective in improving and developing students' religious character. Students can develop good habits in everyday life without coercion with this habituation method. The efforts made by teachers to instill students' religious character using the habituation method in terms of obedience to God make many students worship regularly and obediently without coercion from the teacher.